Pengaruh Permainan Puzzle Terhadap Konsentrasi Belajar Anak Usia Dini - Siti Muhaimin Ibrahim; Nurzia Ilahude; Bunga Alifa Antahari; Riska Panto; Mum'min Al Ganis Toi; Mita Sari (INDO PUBLISHING, 2026)
This study aimed to analyze the effect of puzzle games on the learning concentration of early childhood. Puzzle activities are considered one of the educational play media capable of stimulating children’s cognitive abilities, attention focus, accuracy, and problem-solving skills through image and shape arrangement activities. The study employed a quantitative approach using a correlational design to determine the relationship between puzzle game activities and children’s learning concentration. Research participants consisted of children aged 4–6 years in a kindergarten environment. Data were collected through observation, questionnaires, and documentation. Furthermore, the data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation analysis.The findings revealed that puzzle-playing activities were categorized as very high. Children actively participated in arranging puzzle pieces, identifying shapes and colors, and completing games systematically. In addition, the level of children’s learning concentration was also classified as very high. Children demonstrated the ability to pay attention to teacher instructions, maintain focus during classroom activities, and complete learning tasks more effectively. The correlation analysis showed a correlation coefficient value of 0.78, indicating a strong relationship between puzzle games and learning concentration in early childhood. These findings suggest that puzzle games can be utilized as an effective educational medium to support children’s concentration development during the learning process.Based on the results, puzzle games may serve as an alternative learning strategy for teachers and parents in creating enjoyable, interactive, and developmentally appropriate learning experiences for early childhood education.